60 Years of Research in Plasticity The Contributions of Th. Lehmann and his Group. (2017) - Bruhns, Otto T.
Abstract: Th. Lehmann was born the 10th of August 1920 in Silesia at that time a part of Germany and died the 29th of August 1991 at Hannover. He was educated Mechanical Engineering in Breslau (now Wroclaw/Poland) and Hannover and got his doctor's degree in 1952 with a thesis in fluid mechanics. After four years of successful engineering in metal forming industry, he went back to Hannover University in 1956 (to Prof. Kienzle). The lack of accurate descriptions for finite deformation has stimulated his interest for more rigorous formulations of plasticity. Shortly after he moved to Prof. Pestel, where together with Oskar Mahrenholtz and Horst Lippmann a new group has been established, treating plasticity from its different aspects. His habilitation in 1959 on Some Considerations on the Fundamentals of Metal Forming, together with some related works became the starting point of a steadily growing successful period of research. The present lecture will commemorate this great colleague and his contributions to modern plasticity.